Effects of the load differences on elite swimmers` perceived ratings for stroke techniques and the actual power outputs during semi-tethered swimming - Yoshimura, Y.; Moriya, T.; Takahashi, Y.; Oishi, K.; Yasukawa, M. (2001)
It was already reported that the utility of semi-tethered swimming (STS) by using the power processor system for swimming (PPS) was developed by the authors. This study was conducted to determine the optimum load of specific power training using STS. Twenty five elite male competitive swimmers were tested for mean power outputs (10 sec), and several parameters of strokes were measured during STS with ranged from 2 to 14 kg loads. Additionally, to evaluate STS training effects and swimming techniques between free swimming and STS, several perceived ratings were recorded. The power outputs measured by PPS increased accompanied with the increment of load and showed peak values at 8 kg load. They dropped off remarkably at the load of over 10 kg except for breast strokes. The swimmers` perceived ratings for stroke techniques were significantly (p<0.05) decreased at the loads from 8 to 14 kg in any stroke. Though the swimmers` perceived ratings showed that STS training was very effective at any load as sprint training, several stroke techniques were considered to be different from those during free swimming at heavier loads. It was suggested that STS training using heavier loads over 8 kg induced higher power output from above results. However, the possibility which the loads effected the stroke techniques must be in consideration.